2018
DOI: 10.5457/p2005-114.199
|View full text |Cite
|
Sign up to set email alerts
|

Age at surgery and outcomes of an undescended testis: A single center experience

Abstract: Objective -To evaluate age at surgery and outcomes of undescended testis (UDT) of boys who underwent surgical treatment at our institution. Methods -The retrospective study was conducted from December 2006 until December 2016 analysing the medical documentation of boys with UDT who were treated with orchidopexy. Age of boys at the time of diagnosis, age at which orchidopexy was performed, results of intraoperative observations and treatment complications were analysed. Results -Orchidopexy was performed in 562… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a study conducted in Al Khobar, Saudi Arabia, Alsowayan et al demonstrated that median age at time of orchiopexy was 25 (range, 7.65-130.2) months (11). Furthermore, the median age at orchiopexy was found as 50.5 months (range 22 -117) in a study from Bosnia and Herzegovina (12). Moreover, a multicenter analysis from Germany emerged that the mean age at orchiopexy was later than recommended ages, ranging from 42 to 67 months (13).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Al Khobar, Saudi Arabia, Alsowayan et al demonstrated that median age at time of orchiopexy was 25 (range, 7.65-130.2) months (11). Furthermore, the median age at orchiopexy was found as 50.5 months (range 22 -117) in a study from Bosnia and Herzegovina (12). Moreover, a multicenter analysis from Germany emerged that the mean age at orchiopexy was later than recommended ages, ranging from 42 to 67 months (13).…”
Section: Discussionmentioning
confidence: 99%